Patriarchal gatekeepers and scholarship pipelines: Why Zambian students choose China over the UK - Kapilya, Reagan (Journal of International Students, 2026)
International study is a critical but unequal pathway for Zambian youth, with a growing preference for China over traditional destinations such as the UK. This mixed-methods study investigates the factors underlying this destination choice and proposes the concept of “patriarchal mediation” as a contextual layer in household decision-making. Data from 111 Zambians aged 18–45 were collected via an online survey with open-ended questions. Multinomial logistic regression revealed that having a father’s education (OR = 1.42, p = .005) and having a lower family income (OR = 0.76, p = .017) were the strongest predictors of preferring China over the UK, whereas having a mother's education was not significant. Urban residence also reduced the odds of preferring China. Thematic analysis highlighted scholarships as a primary driver and suggested fathers' role as gatekeepers in the decision process. The findings challenge the context-neutral application of standard push‒pull models and point to the household as a critical site where global educational inequalities are reproduced in high-poverty, patriarchal contexts. Recommendations for equity-focused interventions that address intrahousehold dynamics are discussed.